Validity and Effectiveness of STEAM-Based Food Microbiology Electronic Booklet to Improve Critical Thinking Skills of Biology Students - Rizka Ramadani Dalimunthe; Hasruddin Hasruddin; Mufti Sudibyo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research and development aims to determine the validity and effectiveness of STEAM-based food microbiology electronic booklets based on the assessment of validators and the results of student critical thinking skills tests. Method: This research is an R&D study using the ADDIE development model. The developed product was tested on students using the One Group Pretest-Posttest research design. The validity test was carried out by giving a questionnaire to the validator, and the effectiveness test was carried out by giving a test in the form of 20 fill-in questions to 15 Biology students. Results: The results of this study are that STEAM-based electronic booklets are very feasible to use as teaching materials and learning media and are effective in teaching food microbiology because they can improve students' critical thinking skills. This study is recommended to carry out STEAM-based electronic booklet development innovations in other food microbiology materials. Novelty: The novelty of this study lies in the research variables, which focus on the validity and effectiveness of food microbiology electronic booklets integrated with the STEAM approach to obtain teaching materials that encourage students to be active in learning activities.